Evaluating rice crop phenology and crop yield in hilly region using satellite imagery and Google Earth Engine - SHWETA POKHARIYAL; N.R. PATEL; AJEET SINGH NAIN; AKARSH S.G.; R.S. RANA; R.K. SINGH; RAJEEV RANJAN (Journal of Agrometeorology)
Monitoring vegetation phenology is essential for understanding the impacts of climate change on agricultural production. This study leverages Sentinel-2 data to develop an algorithm in Google Earth Engine (GEE) for calculating phenological metrics of rice crop cultivated over the hilly area, allowing for high-resolution, efficient, and large-scale analysis without the need for data download. The study focuses on key metrics, including the start of the season  and end of the season , length of growing season derived from various vegetation indices. The results demonstrate that NDVI-based phenological metrics closely align with the observed values at the experimental site, Malan. Moreover, the relationship of NDVI based length of growing season with the rice crop yield was found stronger with a R2 value of 0.68, depicting the capability of the satellite-based phenology metrics to estimate the rice crop yield in hilly region of Himachal Pradesh.